Peer-to-peer lending to businesses: Investors' characteristics, investment criteria and motivation. (November 2019) - Pierrakis, Yannis
Online peer-to-peer (P2P) business lending, where individual investors provide unsecured loans directly to individual business borrowers without the intermediation of banks, has experienced rapid growth in recent years. However, very little is currently known about the individuals who lend money through the online P2P lending platforms. Drawing on the cognitive evaluation theory and responses to a survey from 630 investors of the Funding Circle platform, the largest P2P business-lending platform in the United Kingdom, this article describes their personal characteristics, investment criteria and their motivation to invest. A typical P2P business lender is male, highly educated and relatively wealthy with a science, business or finance degree. According to the factor analysis, variables related to company quality and associated risks are important investment criteria, while the expectation of making a financial return is the main motivation behind individuals' decision to lend money to companies. In contrast, intrinsic motives such as geographical location, personal relationship or knowledge of the company are of significantly less importance.